Are Americans and Indians more altruistic than the Japanese and Chinese? Evidence from a new international survey of bequest plans - Charles Yuj Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2014)
This paper discusses three alternative assumptions concerning household preferences (altruism, self-interest, and a desire for dynasty building) and shows that these assumptions have very different implications for bequest motives and bequest division. After reviewing some of the literature on actual bequests, bequest motives, and bequest division, the paper presents data on the strength of bequest motives, stated bequest motives, and bequest division plans from a new international survey conducted in China, India, Japan, and the United States. It finds striking inter-country differences in bequest plans, with the bequest plans of Americans and Indians appearing to be much more consistent with altruistic preferences than those of the Japanese and Chinese and the bequest plans of the Japanese and Chinese appearing to be much more consistent with selfish preferences than those of Americans and Indians. These findings have important implications for the efficacy and desirability of stimulative fiscal policies, public pensions, and inheritance taxes.
Keywords: D12; D14; D64; D91; E21; H31; J14; P52; Z12; 330; bequests; inheritances; estates; inter vivos transfers; intergenerational transfers; bequest motives; bequest division; bequest plans; equal division; household preferences; altruism; selfishness; self-interest; selfish life cycle model; altruism model; dynasty model; dynasty building; primogeniture; selfish exchange model; strategic bequest motive; inheritance laws; estate taxes; social safety nets; social norms; culture; religiosity; religion